Evaluasi Produktivitas Kutu Lak, Laccifer lacca Kerr. (Hemiptera: Kerridae) pada Tiga Jenis Tanaman Inang - Rostaman Rostaman; Bambang Sugeng Suryatna (Perhimpunan Entomologi Indonesia, 2009)
Lac insects (Laccifer lacca Kerr) live parasitically on “kosambi” plants, and produce resins that are called lac. Lac are used for electronics, printing, textile, clothing, cosmetics, and food industry. The insects also live on various plants. The goal of this research was to evaluate the population quality of Lac insect that live on three host plants. The best parameter for population quality was biomass or lac production. Three host plants were inoculated by broods. The result showed that “kosambi” was the best host plant for the insect due to higher biomass (i.e lac production) than “kabesak putih” and “kabesak hitam” plants.